EFEKTIVITAS AUKSIN DAN GIBERELIN TERHADAP UMUR BERBUNGA DAN PANEN TANAMAN KORO PEDANG (Cannavalia ensiformis) - Arnanto, Driska; Maryani, Yekti; Koswara, Galih Indra; Kusumawati, Dian Eka (Viabel : Jurnal Ilmiah Ilmu-Ilmu Pertanian, 2024)
The aim of this research was to determine the effect of the growth regulator substances auxin and gibberellin as chemical mutagens on flowering time and harvest time of jack bean. This research was carried out in the Greenhouse of the Faculty of Agriculture, Bachelorwiyata Tamansiswa University, Yogyakarta City. This research was carried out from August to December 2023. The research was carried out using the Completely Randomized Design (CRD) method. Consisting of 4 replications, each replication contained 3 treatments. So 12 experimental units were obtained, namely: P1 = IAA 2 ppm + GA 10 ppm, P2 = IAA 4 ppm + GA 10 ppm, P3 = IAA 6 ppm + GA 10 ppm. The collected data was analyzed using 5% ANOVA and further tested using 5% Duncan Multiple Range Test (DMRT). The influence of the growth regulators auxin and gibberellin as chemical mutagens showed varying results at concentrations of IAA 4 ppm and GA 10 ppm which affected the day of harvest. However, there was no difference in flowering age between all treatments.